Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

We know $$i^2=-1 $$then why does this happen? $$ i^2 = \sqrt{-1}\times\sqrt{-1} $$ $$ =\sqrt{-1\times-1} $$ $$ =\sqrt{1} $$ $$ = 1 $$

EDIT: I see this has been dealt with before but at least with this answer I'm not making the fundamental mistake of assuming an incorrect definition of $i^2$.

share|improve this question
30  
Why is $\sqrt{-1} \cdot \sqrt{-1} = \sqrt{-1 \cdot -1}$? We know that $\sqrt{ab} = \sqrt{a} \sqrt{b}$ but this is only true for $a,b \geq 0$... –  algebra_fan Jul 3 '11 at 9:17
    
Thank you algebra_fan. I've never seen restrictions placed on log/exponent laws before. Where/when do those get properly defined? Most math textbooks? –  Greg Jul 3 '11 at 9:24
2  
Duplicate of math.stackexchange.com/q/438/7850 –  The Chaz 2.0 Jul 3 '11 at 11:49
15  
In every math textbook! If there is a math textbook that says $\sqrt{ab} = \sqrt{a}\,\sqrt{b}$ without providing restrictions on $a,b$, then you should write to the author immediately! –  GEdgar Jul 3 '11 at 12:43
1  
$i^2=-1$ is the definition of $i$. –  Tpofofn Feb 8 '13 at 18:00
show 7 more comments

10 Answers

up vote 27 down vote accepted

From $i^2=-1$ you cannot conclude that $i=\sqrt{-1}$, just like from $(-2)^2 = 4$ you cannot conclude that $-2=\sqrt 4$. The symbol $\sqrt a$ is by definition the positive square root of $a$ and is only defined for $a\ge0$.

It is said that even Euler got confused with $\sqrt{ab} = \sqrt{a}\,\sqrt{b}$. Or did he? See Euler's "mistake''? The radical product rule in historical perspective (Amer. Math. Monthly 114 (2007), no. 4, 273–285).

share|improve this answer
    
If I cannot conclude that $i=\sqrt{-1}$ then what good is it? Wouldn't that mean I couldn't use $i$ for what it's intended? Namely $\sqrt{-5} = \sqrt{-1\times 5} = i\sqrt{5}$ ? –  Greg Jul 4 '11 at 13:04
8  
@Greg, then only property of $i$ that you need is that $i^2=-1$. The symbol $\sqrt{-1}$ is abuse of notation. As for $\sqrt{-5}$, you get $(i\sqrt{5})^2= (-1)\cdot 5 = -5 =$, as you expect. –  lhf Jul 4 '11 at 15:46
2  
There's nothing wrong with defining(!) $\sqrt{-1}=i$, just as there's nothing wrong with defining $\sqrt{4}=2$ despite the fact that from $x^2=4$ you cannot conclude $x=2$. The difference to real numbers is that you cannot define the square root function so that it is continuous on all of $\mathbb C$. And the calculation in the question is just incorrectly applying power laws; you don't even need complex numbers to do something similar: $-1 = (-1)^1 = (-1)^{2\cdot1/2} = ((-1)^2)^{1/2} = 1^{1/2} = 1$ –  celtschk Jul 10 '13 at 12:40
add comment

Any non zero number has two distinct square roots. There's an algebraic statement which is always true : "a square root of $a$ times a square root of of $b$ equals a square root of $ab$", but this does not tell you which square root of $ab$ you get.

Now if $a$ and $b$ are positive, then the positive square root of $a$ (denoted $\sqrt{a}$) times the positive square root of $b$ (denoted $\sqrt{b}$) is a positive number. Thus, it's the positive square root of $ab$ (denoted $\sqrt{ab}$). Which yields

$$\forall a,b \ge 0, \ \sqrt{a} \sqrt{b} = \sqrt{ab}$$

In your calculation, because $i$ is a square root of $-1$, then $i^2$ is indeed a square root of $1$, but not the positive one.

share|improve this answer
add comment

Following Willie Wong's suggestion, I will put the comments I made before into an answer. The problem with this argument is that the formula $\sqrt{ab} = \sqrt{a} \sqrt{b}$ is valid for $a,b \geq 0$. In particular, it is not valid in the case when $a=b=-1$ so that the step $\sqrt{-1}\sqrt{-1} = \sqrt{(-1)(-1)}$ is incorrect.

share|improve this answer
add comment

$\hspace{0.2in}$ The problem is this: the (polar) representation of a complex number depends on your choice of branch. Once you choose a branch of the square root, you cannot simultaneously represent $1$, and $-1$, because they are $\pi$ apart, so that $-1$ and $1$ will necessarily be in different branches of $z^{1/2}$. The choice of square root you make (if you want it to be well-defined) depends on the choice of branch you are working with. You are trying to combine numbers that live in different branches; it is as if you add $1+1$ and get $1-i\pi$, since 1 can also be represented as $i\pi$ ($~1$ can actually be represented as $ik\pi$, but when you operate, you are supposed to stay within a branch, and, in your case, you are not$~$).

$\hspace{0.2in}$ In complex numbers, from the perspective of polar representations, when you multiply $z_1 \dot z_2$, you multiply the respective lengths, and add the respective angles (but you have to make up for the fact that the sum of the angles may be larger than $2\pi$ (or whatever argument-system you are working with. So in this sense, when you multiply $i$ by itself, you multiply the length of $i$ by itself, and add the argument to itself; i.e., you double the argument. In complex variables, you have many possible polar representations for a given number; specifically, given $z=re^{it}$, then $z=re^{i(t+2\pi)}$ is also a valid representation.

$\hspace{15.0in}$ $\hspace{0.2in}$ You must then choose a specific representation for your $z$, specifically; you will need to specify the range of the argument you will be working with. So, say you work with the "standard" range of $[0,2\pi)$. Then the expression for $i$ (me) is as $i=1e^{i\pi/2}$, so that $i^2$= $(1)(1).e^{i(\pi/2+\pi/2)}=e^{i\pi}=-1$. But the way backwards from multiplying to taking roots is more complicated if your base is non-negative, and/or your exponent has non-zero imaginary part. When this last is the case, you define:

$z^{{1}/{2}} \:=e^{{\Large{log(z)}}},~$ where we define:

$\log(z):=\ln |z|+i arg(z)$

(This choice of definition has to see in part with wanting to have the complex log agree with the standard real $\log$--though this agreement is possible only for one choice of "branch", as we will see.) But because of the infinitely-many possible choicesfor the argument of a number, the $\log(z)$ itself--defined locally as the inverse of $e^z$ is somewhat-ambiguously-defined, since $e^z$ does not have a global inverse (since it is not $1-1$, for one thing, but $e^z$ does have local inverses, e.g., by using the inverse function theorem). So when we mention $\log$, we are referring just to one of (infinitely-) many possible local inverses of $e^z$ .Each possible local inverse to $e^z$ is called a "branch" of the $\log$. So once we choose a branch for the $\log$, which is a choice of an open set (technically, it is half-open) of width $2\pi$ from which we will choose the argument we will use. So, say we choose the standard branch $(0,2\pi)$, which we call Log(z). We then define :

$z^{1/2}:=e^{\large{Log(z)/2}}$

But , in this branch , $(-1)^{1/2}$ is not even defined, because the argument for $(-1)$ is $0$ , which is outside of the allowable values $(0,2\pi)$. So, in this sense, the expression $(-1)^{1/2}$ is not well-defined, i.e, does not really make sense. ($~$Note that this particular branch of $\log$ reduces to the standard one when you select an argument of $t=0~$).

share|improve this answer
    
Maybe I overdid it, trying to understand the log better. Could someone help with the spacing? I am saturated on formatting, sorry. –  gary Jul 3 '11 at 10:58
    
Help exactly with what spacing in your answer? –  night owl Jul 4 '11 at 2:34
    
Well, I try to space out the paragraphs, but they do not come out with the spacing of the original; specifically, in spreading the text out some more, and in separating paragraphs. –  gary Jul 5 '11 at 17:26
    
@ gary: Alright got it. –  night owl Jul 7 '11 at 13:48
    
Another downvote without a constructive comment. Is it personal? If there is something specific you do not like, it would be nice to hear; I may be able to learn from it. Still, it is up to you, whomever downvoted me without an explanation. –  gary Jul 12 '11 at 1:12
show 1 more comment

What you can do is $a^x a^y = a^{x+y}$, so $(-1)^{1/2}(-1)^{1/2}=(-1)^{1/2+1/2}=(-1)^1=-1$.

share|improve this answer
    
I don't follow. What is $(-1)^{1/2}$? Is it $i$ or $-i$? –  Hendrik Vogt Jul 3 '11 at 11:29
    
@Hendrik Vogt I think $i=(-1)^{1/2}$ –  Fan Zhang Jul 3 '11 at 11:47
1  
And why not $(-1)^{1/2} = -i$? The problem is that you first have to specify which branch of the square root you want; cf. gary's answer. –  Hendrik Vogt Jul 3 '11 at 11:50
    
This answer can at best muddy waters. @upvoter Why the upvote? –  Did Mar 7 at 16:45
add comment

There are many ways to show that your second equality is incorrect. Just for the sake of argument and a refreshing change of pace, suppose your point is true. That is, suppose $i^{2} = 1$. Then \begin{align} (x + i)(x-i) = x^2 - i^{2} = x^{2} - 1. \end{align} Use the Descartes Rule of signs to derive a contradiction. Hint: $i$ is not real. Can you finish the line of reasoning and derive an absurdity?

share|improve this answer
9  
Isn't a quicker absurdity $-1 = i^2 = 1$? –  user92843 Jul 3 '11 at 9:33
    
Hmm. if $1+i=0$ and $1-i=0$ then you can set them equal to each other. So $1+i=1-i$ which means $i=-i$. But I'm not sure why you conclude $(1+i)(1-i)=0$. –  Greg Jul 3 '11 at 9:33
1  
@user02138: The OP is assuming $i$ is the square root of $-1$ in the derivation. If you're assuming nothing about $i$ then there's no contradiction, since for all you know $i$ could equal 1. –  user92843 Jul 3 '11 at 9:46
add comment

You may only apply sqrt(a) sqrt(b) = sqrt (a*b) when a,b >=0

share|improve this answer
add comment

Don't take me the wrong way, all of you are right from a certain point of view.

Let me show you the following. Let $a$ and $b$ be complex numbers. If $\sqrt a$ is a square root of $a$ and $\sqrt b$ is a square root of $b$, then $(\sqrt a\sqrt b)^2 = (\sqrt a)^2 (\sqrt b)^2 = ab$ by assumption, so indeed $\sqrt a\sqrt b$ is a square root of $ab$. Notice that it is some square root; there is no canonical choice over $\mathbb{C}$!

From this point of view, your arguments work until $i^2 = \sqrt1$. All you've shown is that $-1 = i^2$ is a square root of 1 and no one will disagree with that fact.

So what I'm trying to say is, if you want to write something like $\sqrt a\sqrt b = \sqrt{ab}$, which isn't the worst idea, you can't write something like $\sqrt 1 = 1$.

share|improve this answer
add comment

In general,

$\forall a,b \in \mathbb{R} , ab\geq 0, (\sqrt{ab} =\sqrt{ |{a}| }\sqrt{|b|}) $

share|improve this answer
add comment

@Greg: $i^2=-1$ is a matter of definition. It was introduced to handle a negative sign under the radical when solving polynomial equations. The best example is $x^2 +1 =0$, which yields $x = \pm\sqrt{-1}$. Using your manipulation above would yield $x^2 = 1$ which clearly does not solve the equation.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.